2015
DOI: 10.1371/journal.pone.0130357
|View full text |Cite
|
Sign up to set email alerts
|

The Ketogenic Diet Alters the Hypoxic Response and Affects Expression of Proteins Associated with Angiogenesis, Invasive Potential and Vascular Permeability in a Mouse Glioma Model

Abstract: BackgroundThe successful treatment of malignant gliomas remains a challenge despite the current standard of care, which consists of surgery, radiation and temozolomide. Advances in the survival of brain cancer patients require the design of new therapeutic approaches that take advantage of common phenotypes such as the altered metabolism found in cancer cells. It has therefore been postulated that the high-fat, low-carbohydrate, adequate protein ketogenic diet (KD) may be useful in the treatment of brain tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 57 publications
(61 reference statements)
9
75
0
1
Order By: Relevance
“…1 and 2). These results are consistent with another study (43) that investigated the effects of the KD on tumor growth and progression in animal models. The results revealed that peritumoral edema was significantly reduced in animals fed the KD, and protein analyses showed altered expression of zona occludens-1 and aquaporin-4.…”
Section: Kambach Et Alsupporting
confidence: 92%
“…1 and 2). These results are consistent with another study (43) that investigated the effects of the KD on tumor growth and progression in animal models. The results revealed that peritumoral edema was significantly reduced in animals fed the KD, and protein analyses showed altered expression of zona occludens-1 and aquaporin-4.…”
Section: Kambach Et Alsupporting
confidence: 92%
“…The striking feature of the work done to date in a number of model systems using different dietary interventions is that alterations in metabolism have a far reaching effect on tumor cells, tumors and the tumor microenvironment. Studies have shown reductions in growth rate as one might expect however, there are also changes in the formation of reactive oxygen species and oxidative stress (Stafford et al, 2010; Milder and Patel, 2012; Allen et al, 2013), angiogeneisis (Zhou et al, 2007; Jiang and Wang, 2013; Woolf et al, 2015), hypoxia (Maurer et al, 2011; Poff et al, 2015; Woolf et al, 2015), inflammation and peri-tumoral edema (Mavropoulos et al, 2009; Woolf et al, 2015), metastasis and invasion (Gluschnaider et al, 2014; Lv et al, 2014; Hao et al, 2015; Poff et al, 2015) and the expression of various transcriptional and post-transcriptional modulators such as NF-ÎşB (Woolf et al, 2015) and microRNAs (Pazmandi et al, 2015). …”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
“…D’Agostino and co-workers have added hyperbaric oxygen and ketone supplementation to demonstrate reduced tumor cell growth and metastatic spread in the VM metastatic tumor model (Poff et al, 2014, 2015). We used the syngeneic intracranial GL261-luc/albino C57/Bl6 model to demonstrate that CR was not necessary for the anti-tumor effects of the KD (Stafford et al, 2010), particularly when a 4:1 fat:carbohydrate plus protein formulation is used (Scheck et al, 2012; Woolf et al, 2015; Lussier et al, 2016). Recently Martuscello et al (2016) demonstrated inhibition of glioma stem cell growth in vitro and in vivo through the use of a supplemented high fat low carbohydrate diet.…”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Further, CR was shown to normalize a number of factors involved in tumor vessel instability and weakness (including VEGF) as well as reducing peritumoral edema in a mouse model using human U87 glioma cells (Jiang and Wang 2013). In the GL261 mouse glioma model, we found that when fed ad libitum the KD decreased tumor vasculature, reduced peritumoral edema, and altered the expression of genes involved in angiogenesis (Woolf et al 2015), despite the fact that the expression of VEGF was unchanged . Taken together, these results suggest that another effect of metabolic therapy may be to target angiogenesis activity, thus mimicking the beneficial effects of bevacizumab.…”
Section: Anti-angiogenic Effectsmentioning
confidence: 74%